Antibacterial Effect of CrO and CoFe2O4 Nanoparticles upon Staphylococcus aureus - Saber Imani; Zahra Zagari; Saeid Rezaei-Zarchi; Ali Mohammad Zand; Mohammad Dorodiyan; Hosein Bariabarghoyi; Fatemeh Lotfi (Fasa University of Medical Sciences, 2011)
Background & Objectives: The use of metal oxide nanoparticles can be effective to eliminate the bacterial infections, as an alternative to antibiotics. In this study, antibacterial properties of nonmaterials of CrO and CoFe2O4 are investigated against Staphylococcus aureus as a major and prevalent pathogenic bacterium to achieve sterile nano-containers. Materials & Methods: Different concentrations of CrO and CoFe2O4 nanoparticles, (0.2, 0.4, 0.6, 0.8, and 1%) of each, were examined with respect to their optical density (OD) culture separately. Different percentages of each nanoparticles were also examined together for the best antibacterial combination. Kinetics of Bactericidal of nanoparticles were calculated in two-hour periods and were compared with the power of other common antibiotics. Ratios of MIC/MBC were calculated by Micro dilution method, to demonstrate the bactericidal power of nanoparticles. Results: The best concentration of the nanoparticles with the highest effect of bactericidal was obtained in the presence of 1% concentration of CrO that the OD of S. aureus culture medium had reduced 4/6 times than the control group (p<0/001).Ratio of 70% CrO to 30% CoFe2O4 was the best of the Bacteriostatic properties that OD was reduced 3/3 times than the control group (p<0/05). Best kinetics of bactericidal with survival rate in the presence of 1% CrO and CoFe2O4 were obtained in 24 and 36 hours respectively. In critical concentration of 1% CrO and CoFe2O4 bactericidal power was about 67 and 56 % respectively. The MIC/MBC rate for CrO and CoFe2O4 was obtained 0/2 and 0/4 respectively. Conclusion: The results showed that CrO nanoparticle compared with CoFe2O4 has a higher bactericidal power for S. aureus infection. Therefore, by completion of these experiments and the use of metal oxide nanoparticles complex in sensitive environments such as food storage containers, etc. are suggested.